(3fhGaM GdhQO hGdYfHQ hGdeSc GdOGQi dTQM BNQ JQLeI UMjM GdHNGQis - (3YHO GdbGOQ Hf CMeO Gdchgjs; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3hHYO agPg fhGaM GdhQO hGdYfHQ hGdeSc GdOGQi dTQM BNQ JQLeI UMjM GdHNGQi LeYJg djchf Ef TGA Gddg JPcQg dfaSi hdef GMJGL Edjg ef CHfGA LfSi s
(3BNQgG (B:s
(3ef GdcQje GdeaVGd GdPi jLRd GdYWjGJ hjcTa GdHdjGJ GfJgi HMeO Gddg s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B541s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs